2021
DOI: 10.1016/j.ijid.2021.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive humoral immune responses against seasonal human coronaviruses in COVID-19 patients with different disease severities

Abstract: Background We evaluated the cross-reactive antibody response against seasonal human coronaviruses (HCoVs) according to disease severity in patients with COVID-19 in Japan. Methods We analyzed 194 paired-collected serum samples from 97 patients with COVID-19 (mild, 35; severe, 62) on admission and during convalescence. IgG antibodies against the nucleocapsid (N) and spike (S) proteins of SARS-CoV-2 and four seasonal HCoVs (HCoV-NL63, -229E, -OC43, and -HKU1) were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…Similarly, Loyal et al were able to show that pre-existing spike-cross-reactive T cells were activated after COVID-19 mRNA vaccination and showed signs similar to a secondary immune response ( 32 ). Contrasting studies that measured a high degree of cross-reactivity between SARS-CoV-2 and HCoV, however, found no correlation between HCoV reactivity and increased COVID-19 immunity ( 33 , 34 ). This is in line with other studies showing that HCoV-specific antibody titers increased in convalescent individuals but did not correlate with increased SARS-CoV-2 titers or protection ( 35 37 ).…”
Section: Discussioncontrasting
confidence: 61%
“…Similarly, Loyal et al were able to show that pre-existing spike-cross-reactive T cells were activated after COVID-19 mRNA vaccination and showed signs similar to a secondary immune response ( 32 ). Contrasting studies that measured a high degree of cross-reactivity between SARS-CoV-2 and HCoV, however, found no correlation between HCoV reactivity and increased COVID-19 immunity ( 33 , 34 ). This is in line with other studies showing that HCoV-specific antibody titers increased in convalescent individuals but did not correlate with increased SARS-CoV-2 titers or protection ( 35 37 ).…”
Section: Discussioncontrasting
confidence: 61%
“…Also, Focosi et al showed an association between previous humoral immunity to NL63 and 229E and worse clinical outcome in COVID-19 patients (21). Other studies have suggested that pre-existing immunity to sCoVs may not be related to COVID-19 severity or protection at all (17,27,35). Currently, few studies have provided evidence for an impact of pre-existing cross-reactive antibodies on inactivated COVID-19 vaccineinduced neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, T cell-mediated anti-SARS-CoV-2 responses were found in unexposed human, indicating a cross-reaction between human CoVs and SARS-CoV-2 (10)(11)(12)(13)(14). Accumulating evidence suggests that pre-existing humoral immunity to sCoVs may play a role in the specific anti-SARS-CoV-2 antibody responses (15), but this possibility is controversial (16,17). Some studies showed that elevated levels of pre-existing antibodies against sCoVs, specifically OC43 and HKU1, were associated with a less severe course of COVID-19, suggesting a protective effect of prior exposure to sCoVs (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains largely unclear in which ways circulating HCoV antibodies affect the SARS-CoV-2 immune response [ 85 87 ]. Several other studies have indicated that B cell [ 88 ] and T-cell responses mounted against a lifetime of exposures to HCoVs can cross-react with SARS-CoV-2 [ 70 , 89 ], yet there is no known cross-protective effect for B cells [ 85 , 90 ] and the protective role of the T-cell response remains unclear.…”
Section: Introductionmentioning
confidence: 99%